Simultaneous Barcode Sequencing of Diverse Museum Collection Specimens Using a Mixed RNA Bait Set - Agne, Stefanie; Preick, Michaela; Straube, Nicolas; Hofreiter, Michael (Frontiers in Ecology and Evolution, 2022)
A growing number of publications presenting results from sequencing natural history collection specimens reflect the importance of DNA sequence information from such samples. Ancient DNA extraction and library preparation methods in combination with target gene capture are a way of unlocking archival DNA, including from formalin-fixed wet-collection material. Here we report on an experiment, in which we used an RNA bait set containing baits from a wide taxonomic range of species for DNA-hybridization capture of nuclear and mitochondrial targets for analyzing natural history collection specimens. The bait set used consists of 2,492 mitochondrial and 530 nuclear RNA baits and comprises specific barcode loci of diverse animal groups including both invertebrates and vertebrates. The baits allowed to capture DNA sequence information of target barcode loci from 84 % of the 37 samples tested. Our study illustrates how efforts to attain barcode sequence information from natural history collection specimens may be combined and are a way of implementing barcoding inventories of scientific collection material.